Impact of Vitamin D3 Deficiency on Liver and Adipose Tissue in Pregnant Mice Amenah Salman Mohammed - Amenah Salman Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Vitamin D is a critical nutrient integral to various physiological processes such as bone health, immune function, and gene regulation. Its deficiency is linked to a range of health complications, underscoring the need to understand its effects on pregnant individuals and fetal development. This review article focuses on the consequences of Vitamin D3 deficiency, specifically on the liver and adipose tissue in pregnant mice. The study aims to uncover the molecular, cellular, and physiological changes occurring in these tissues due to Vitamin D3 deficiency.